MO219: Are C4D, Nephrın and WT1 Expressıons İmportant ın the Dıfferentıal Dıagnosıs between Focal Segmental Glomerulosclerosıs and Mınımal Change Dısease?. (3rd May 2022) - Akcali, Esra; Turgutalp, Kenan; Yuyucu Karabulut, Yasemin; Ebru Eser, Zeynep; Agtas Mistik, Ozge; Coskun Yılmaz, Banu; Bardak, Simge; Ozturk, Savas; Demir, Serap; Kıykım, Ahmet
Abstract: BACKGROUND AND AIMS: Focal Segmental Glomerulosclerosis (FSGS) and Minimal Change Disease (MCD) are most common seen glomerulonephritis. Differential diagnosis between FSGS and MCD by light microscopy (LM) cannot be made in some times. In this situation, electron microscopy (EM) is needed for differential diagnosis. Rarely, EM may not be sufficient for differential diagnosis. There are needed new markers for differential diagnose between FSGS and MCD. The aim of this study is to determine which of the glomerular C4d, nephrine staining is specific and sensitive for FSGS and MCD. C4d, Recent experimental data show that complement activation plays a pathogenic role in the development of FSGS. Therefore, C4d staining in the sclerotic focus of the glomeruli in FSGS patients may have an important differential diagnosis. Nephrine is the main component of the slit diaphragm that connects the foot protrusions of the podocytes. Epithelial cell and podocyte dysfunction occurs as a result of defects in the genes encoding these key proteins expressed in GBM. Wilms' tumour suppressor gene (WT1) is a transcription factor that plays very important role in the embryonal development of the genital organs and kidney. WT-1 is expressed in podocytes and is an important transcription factor for podocyte function. METHOD: This is a retrospective study, comprised of patients diagnosed as FSGS, MCD and the ones who diagnosed as having FSGS or MCD couldnot be differentiated. The patients were divided into three groups. Group 1 : FSGS patients, Group 2 : patients with indefinite diagnosis; either FSGS or MCD and Group 3 : MCD patients. All biopsy materials were stained with C4d, WT1 and nephrine. The specificity, sensitivity, positive predictive value (PPV) and negative predictive value (NPV) of C4d, WT1 and nephrine were evaluated for the diagnosis of both FSGS and MCD. RESULTS: C4d staining in group 1 was significantly higher compared with group 2 and group 3 (P < .05). Nephrine was shown significantly more staining in group 3 patients than group 1 (P < .05). C4d was found to be associated with the presence of global or segmental sclerosis in the glomeruli, adhesion to the Bowman's capsule (P < .05). The specificity and sensitivity of C4d in FSGS patients were 85%, 73.9%, while it was 26.1% and 15.4% in MCD. Specificity and sensitivity of nephrine were 87%, 69% in MCD patients compared with 30.8% and 13% in FSGS (Fig. 1 ). PPV and NPV values of C4d and nephrine in FSGS and MCD were shown in Figure 2 . CONCLUSION: C4d and nephrine have predictive diagnostic value for FSGS and MCD respectively. C4d and nephrine are more specific and sensitive to FSGS and MCD, respectively. However, there is a need for randomized studies with larger study groups